911 EVALUATION OF TYPE/LOCATION OF CLINIC APPOINTMENTS IN OLDER PERSONS SERVICES PARKINSON DISEASE PATIENTS IN RURAL EAST SUFFOLK. (14th June 2022) - Blows, S; Thapa, A; Lae-Phyo, W
Abstract: Introduction: We have 262 patients under the care of older persons movement disorders service in East Suffolk, whom due to a combination of retirement and COVID pandemic hadn't seen a consultant for their follow up in up to 18 months. There are the facilities to see patients closer to their homes with satellite outpatient clinics in Eye, Stowmarket, Felixstowe and Aldeburgh, and via telephone and video consultation. We found that 137 of these patients live in rural areas closer to these satellite clinics. An opportunity was sensed to tailor the future service to the preferences of our patients, with the aim of improving experience and satisfaction. Method: We sent a postal survey to these 137 patients asking them about the importance of having one responsible consultant, the type and location of their appointment. Results: We sent a postal survey to these 137 patients, we received 81 Reponses. 91% of respondents ranked it either important, quite important or very important that they see the same consultant. It was the 1st preference to be seen at a local healthcare facility with 71% of patients choosing this as their first choice versus 22% for Ipswich hospital. 7% had a 1st preference of telephone appointment. 0 patients had a 1st choice preference of video conference it was the least favourable preference for 52% of respondents. Conclusion: Our cohort of patients place a high value on continuity of care and would prefer to be seen at a community clinic that is closer to home. These preferences have been discussed with PDUK and CCG and have informed how we deliver our service as of August 2021 with all patients having a locality based clinic and named consultant. Our results are at odds with the ethos of NHSX [1] and the drive to see patients virtually.